Behavior of Four Olive Cultivars During Salt Stress - Regni, Luca; Del Pino, Alberto Marco; Mousavi, Soraya; Palmerini, Carlo Alberto; Baldoni, Luciana; Mariotti, Roberto; Mairech, Hanene; Gardi, Tiziano; D’Amato, Roberto; Proietti, Primo (Frontiers in Plant Science, 2019)
Olive is considered as a moderately salt tolerant plant, however tolerance to salt appears to be cultivar-dependent and genotypic responses have not been extensively investigated. In this work, saline stress was induced in four olive cultivars: Arbequina, Koroneiki, Royal de Cazorla and Fadak86. The plants were grown in 2.5 l pots containing 60% peat and 40% of pumice mixture for 240 days and were irrigated three times a week with half-strength Hoagland solution containing 0, 100 and 200 mM NaCl. The effects of salt stress on growth, physiological and biochemical parameters were determined after 180, 210 and 240 days of treatment. Saline stress response was evaluated in leaves by measuring the activity of GSH and CAT enzymatic activity, as well as proline levels, gas exchanges, leaves relative water content and chlorophyll content, and proline content. All the studied cultivars showed a decrease in Net Photosynthesis, leaves chlorophyll content and plant growth (mainly leaves dry weight) and an increase in the activity of GSH and CAT. In addition, the reduction of proline content in leaf tissues, induced an alteration of osmotic regulation. Among the studied cultivars Royal and Koroneiki better counteracting the effects of saline stress thanks to a higher activity of two antioxidant enzymes.